Development of Banjar Village Community Culture through OCF (Osing Culture Festival) As a Tourism Village Promotion - Ardytia, Wisnu; Imaniar, Dimas; Wahyudiono, Andhika (Budapest International Research and Critics University, 2021)
A qualitative method with an ethnographic approach is used in this study. The results of this study indicate that the implementation of the cultural development of the Banjar community is carried out by mapping the potential of natural and environmental resources, developing the potential and capabilities of human resources at the village level as a dynamist of the village economy, and empowering local communities in managing the potential of their villages to increase added value. The main problem is the low progress of the village which is considered a tourist village. From several villages in Banyuwangi, there are still villages that are poor and have not been eradicated by poverty alleviation programs. Given the importance of productivity development in the context of economic development and growth, this research problem is formulated to what extent the development of community culture is able to become the basis for developing tourism economic productivity which is specifically explained: (1) based on the characteristics of community cultural development, with three main variables namely culture , social and economic, (2) set indicators of the success of community cultural development, and (3) formulate strategies for the use of community cultural development in Banjar Village.